Epileptology - The Modern State of Science 2016
DOI: 10.5772/64445
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs and Risk Factors of Vascular Diseases

Abstract: Epilepsy is one of the most common neurological diseases, afecting approximately % of the population. It is a chronic disease and increased incidence falls in the period up to year and years of age. Most patients require long-term antiepileptic drugs AEDs therapy. In addition, approximately % of patients with epilepsy do not obtain satisfactory seizure control, which is deined as drug-resistant epilepsy. It is postulated that one of the causes of drug resistance can be polymorphisms of ABCB1/MDR1 gene, tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…It is a byproduct in the normal metabolism of the amino acid methionine to cysteine [ 3 ]. Many studies have demonstrated that the prolonged use of certain ASMs raises homocysteine levels, which is related to vascular endothelial damage and, therefore, raises the chances of atherosclerosis and cardiovascular diseases [ 4 ]. Elevated serum homocysteine levels increase oxidative stress, thus, cause vascular inflammation, increase platelet aggregation, induce thrombosis and coagulation disorders, and consequently, produce endothelial damage.…”
Section: Introductionmentioning
confidence: 99%
“…It is a byproduct in the normal metabolism of the amino acid methionine to cysteine [ 3 ]. Many studies have demonstrated that the prolonged use of certain ASMs raises homocysteine levels, which is related to vascular endothelial damage and, therefore, raises the chances of atherosclerosis and cardiovascular diseases [ 4 ]. Elevated serum homocysteine levels increase oxidative stress, thus, cause vascular inflammation, increase platelet aggregation, induce thrombosis and coagulation disorders, and consequently, produce endothelial damage.…”
Section: Introductionmentioning
confidence: 99%